2023
DOI: 10.3390/ijerph20032295
|View full text |Cite
|
Sign up to set email alerts
|

Association between Malnutrition and Depression in Patients with Cancer: The Importance of Nutritional Status Evaluation in Cancer Care

Abstract: Cancer patients are at risk of several comorbid conditions, including nutritional issues and mental health illnesses. The objective of the current study was to estimate the prevalence, upon hospital admission, of depression and malnutrition among adults with cancer. A retrospective chart review was conducted using health information collected as part of routine assistance. Nutritional status was measured through structured tools, including body mass index (BMI), Nutrition Risk Screening (NRS) 2002, and dietary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…[31] Another study showed that malnourished older adults were nearly 3 times more likely to be depressed than well-nourished older adults. [32] Similarly, in a study conducted with older adults, it was stated that this risk was 5 times higher. [33] Risk factors for depression include genetic predisposition, imbalances in brain chemicals, severe stress and traumatic events, personality traits, gender differences, chronic illnesses, and the use of certain medications.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…[31] Another study showed that malnourished older adults were nearly 3 times more likely to be depressed than well-nourished older adults. [32] Similarly, in a study conducted with older adults, it was stated that this risk was 5 times higher. [33] Risk factors for depression include genetic predisposition, imbalances in brain chemicals, severe stress and traumatic events, personality traits, gender differences, chronic illnesses, and the use of certain medications.…”
Section: Discussionmentioning
confidence: 95%
“…[31] Another study showed that malnourished older adults were nearly 3 times more likely to be depressed than well-nourished older adults. [32] Similarly, in a study conducted with older adults, it was stated that this risk was 5 times higher. [33]…”
Section: Discussionmentioning
confidence: 99%
“…Micronutrient deficiencies and GI symptoms following upper GI surgery may remain present even years and decades after upper GI surgery [16][17][18]. As malnutrition has been found to be related to depression in cancer patients, impaired QoL may be both the reason and result of restricted food intake and malnutrition [19].…”
Section: Introductionmentioning
confidence: 99%